Development of Tio2 loaded Cufe2o4 photocatalyst for CO2 conversion into methanol under visible light irradiation - Md. Rahim, Uddin (2016)
The production of methanol through CO2 photoreduction under visible light irradiation, has gained tremendous attention in recent times due to the limited availability of fossil-fuel resources and global climate change caused by rising CO2 level in the atmosphere. The present study aimed to explore visible light active photocatalyst for carbon dioxide (CO2) conversion to methanol in aqueous phase. In this context, copper ferrite (CuFe2O4) and TiO2 loaded copper ferrite (CuFe2O4/TiO2) were synthesized following sol–gel method. The effect of different parameters, such as TiO2 to CuFe2O4 weight ratio, calcination temperature, light intensity, irradiation time and catalyst loading was investigated to evaluate the activity of the catalyst to produce methanol. Methanol was observed as the main product over CuFe2O4, but loading with TiO2 remarkably increased the methanol yield. The maximum methanol yield was obtained on CuFe2O4/TiO2 calcined at 700 oC with a catalyst loading of 1g/L. The catalyst was characterized by XRD, FE-SEM, UV-Vis, photoluminescence (PL) spectrophotometer, and EDX. The XRD results confirmed the formation of spinel type tetragonal CuFe2O4 phases along with predominantly anatase phase of TiO2 in the CuFe2O4/TiO2 hetero-structure. UV-Vis absorption spectrum suggested the formation of the hetero-junction with relatively lower band gap than that of TiO2. PL spectra analysis confirmed the slow-down of the recombination of electron–hole (e−/h+) pairs in the CuFe2O4/TiO2 hetero-structure. The mechanism of the photocatalysis was proposed based on the fact that the predominant species of CO2 in aqueous phase were dissolved CO2 and HCO3- at pH ~5.9. It was obvious that the CuFe2O4 could harvest the electrons under visible light irradiation, which could further be injected to the conduction band of TiO2 to increase the life time of the electron and facilitating the reactions of CO2 to methanol. The developed catalyst showed good recycle ability up to four cycles where the loss of activity was ~25%. To increase the yield of methanol a periodic addition of catalyst into the reactor was proposed where the methanol yield could be raised significantly.